2012
DOI: 10.1007/s10620-012-2114-7
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Outcomes After Anatomical and Non-anatomical Resection of Small Hepatocellular Carcinoma in Patients with Preserved Liver Function

Abstract: AR of a solitary small HCC did not carry postoperative outcome advantages compared with NAR in patients with preserved liver function. We recommend NAR for hepatic resection of small solitary HCC in patients with preserved liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…On the other hand, Tomimaru et al [2] reported that the significant independent predictors for PHLF development were platelet count and volume of resected liver. In a subgroup analysis, platelet count was significantly correlated with PHLF in both larger volume (≥100 g) and smaller volume resection groups (<100 g), although ICG-R15 level was associated with PHLF only in the larger volume group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Tomimaru et al [2] reported that the significant independent predictors for PHLF development were platelet count and volume of resected liver. In a subgroup analysis, platelet count was significantly correlated with PHLF in both larger volume (≥100 g) and smaller volume resection groups (<100 g), although ICG-R15 level was associated with PHLF only in the larger volume group.…”
Section: Discussionmentioning
confidence: 99%
“…Although various treatment strategies, such as liver resection, local ablation, transcatheter arterial chemoembolization and liver transplantation are available for HCC, liver resection is widely performed as the first-line option because of its low morbidity and mortality rates [2-4]. However, the morbidity rates after hepatectomy remain high [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies (20)(21)(22) have demonstrated the superiority of anatomical resection over non-anatomical resection for treatment of HCC. Others (23)(24)(25) have questioned the validity of this suggestion, as they found no differences in HCC recurrence or overall survival rates for patients undergoing either form of resection after resection with curative intent. However, most reported studies had limited statistical power, and no case-matched or randomized clinical trials have compared the outcomes of anatomical and non-anatomical resection for treatment of HCC.…”
Section: Anatomical Vs Non-anatomical Resectionmentioning
confidence: 99%
“…Some studies [5,[12][13][14][15] have demonstrated the superiority of AR over non-anatomic resection (NAR) for HCC. However, the optimum liver resection technique in patients with liver dysfunction remains controversial, and there is no clear evidence that AR results in better long-term survival than does NAR [16][17][18][19]. Most of these reported studies had limited statistical power, and no case-matched or randomized clinical trials have compared the outcomes of AR and NAR for treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%